Current Trends in Biomedical Data and Applications - Sidhu, Amandeep; Bellgard, M.; Dillon, Tharam S. (Springer, 2009)
Bioinformatics tools and systems perform a diverse range of functions including: data collection, data mining, data analysis, data management, and data integration. Computer-aided technology directly supporting medical applications is excluded from this definition and is referred to as medical informatics. This book is not an attempt at authoritatively describing the gamut of information contained in this field. Instead, it focuses on the areas of biomedical data integration, access, and interoperability as these areas form the cornerstone of the field. However, most of the approaches presented are generic integration systems that can be used in many similar contexts.